If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 6 = -35 Reorder the terms: 6 + m = -35 Solving 6 + m = -35 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + m = -35 + -6 Combine like terms: 6 + -6 = 0 0 + m = -35 + -6 m = -35 + -6 Combine like terms: -35 + -6 = -41 m = -41 Simplifying m = -41
| 7.7=x-2.5 | | 2-3x=3-11 | | S=3a+6b | | 7b*b= | | 13x+19y=173 | | 5(3x-2)-14x=4 | | 52+10=n | | -8+7y+5=y-39 | | 23-4x=2x+11 | | (4x+7)(2+x)=0 | | -4m-3=3+4m | | -19x=5x-20 | | 6p-5=-3p+7 | | x^3-17x^2+8x-16=0 | | 15=10y-5y-5 | | 0.444x=-28 | | 11x-12x=0 | | 300=x-(x*0.2) | | x^2+x+200=0 | | x^2+x+200=1 | | 250=x-(x*0.2) | | 250=x-(x*0.25) | | 1000=x-(x*0.2) | | 1800=x-(x*0.2) | | 1200=x-(x*0.25) | | -12+y=8 | | 2000=x-(x*0.25) | | 2000=x-(x*0.3) | | 2-3(4)=-2 | | 4-3(2)=-2 | | 2-3(2)=-2 | | 4-3(0)=-2 |